Selective fasciculotomy of tibial nerve at treatment of spasticity of lower limbs in infants with cerebral palsy - Leonid Pichkur; Yuriy Lontkovsky (Ukrainian Neurosurgical Journal, 2015)
Objective. To assess efficacy of selective fasciculotomy and tibial nerve suture in patients with infantile cererbral palsy (ICP) in incurable spasticity of lower limbs.Materials and methods. In 9 cases with ICP with equine-varus foot deformity 14 selective fasciculotomies and suture of transected movement fascicules of tibial nerve in upper third of shin were performed. Selective criteria was an positive bupivacaine blockage probe. EMG and functional test were used for objectification of intervention results.Results. In 12 cases significant improvement, increase of movement rate in joints in remote period, were achieved. Transposition of tendon of m.tibialis posterior to dorsal surface of foot were performed in 2 cases. Best results determined by staging and physiotherapy.Conclusions. Selective fasciculotomy and fascicular suture of tibial nerve in patients with ICP with incurable spasticity leads to permanent improvement of function of lower limb extremities.